The Predictive Value of SPECT/CT imaging in colorectal liver metastases response after 90Y-radioembolization. - Piotr Piasecki; Jerzy Narloch; Krzysztof Brzozowski; Piotr Zięcina; Andrzej Mazurek; Anna Budzyńska; Jan Korniluk; Mirosław Dziuk (PLoS ONE)
Conclusion The mT/N1 ratio, PAD, and AAD can be used as predictors of tumor response to SIRT treatment, and SPECT/CT imaging can be used for dosimetric assessment of radioembolization.